Assemblage Thinking and Participatory Development: Potentiality, Ethics, Biopolitics. Issue 1 (January 2015) - Grove, Kevin; Pugh, Jonathan
Abstract The politics and ethics of participatory development have been a topic of vibrant debate since the 1990s. While proponents assert that participation emancipates and empowers marginalized people, critics assert that it enacts new forms of control and regulation. This paper reads these debates through the analytical lens offered by assemblage thinking. Assemblage allows us to foreground affective relations between people and things, and the diagrams of power, or ideal sets of force relations, that attempt to direct these affective relations. On this basis, we characterize different participatory approaches in terms of their relation to the constitutive power of affective relations: modernist participation enacts a will to truth that attempts to objectify and control constitutive power through categories such as social capital and vulnerability; performative participation recognizes that participatory activities, while still entangled in power relations, may develop in ways that might challenge existing power relations, and the designs of the project organizer. This characterization helps us identify a politics of life enacted through participatory activities: on one hand, a negative biopolitics that problematizes constitutive power; on the other, an affirmative biopolitics that creates new possibilities for individual and collective life. Assemblage thinking can thus reconfigure participation around an affirmative biopolitics that positions the researcher as one resource among others marginalized people might use in their struggles against insecurity and suffering.